UPAYA PENINGKATAN PENGETAHUAN DAN PENCEGAHAN ANEMIA PADA REMAJA MELALUI EDUKASI - Fitria Wahyu Ariyanti; Ika Suhartanti; Dwiharini Puspitaningsih; Mujiadi; Anndy Prasetya (Jurnal Pengabdian Masyarakat, 2025)
Anemia in adolescents, both boys and girls, is a condition of deficiency of red blood cells or hemoglobin. Adolescent girls are more susceptible to anemia due to blood loss during menstruation, while adolescent boys are also at risk due to various factors such as diet and rapid growth. The purpose of this activity is to provide health education about anemia and its prevention efforts for adolescents. This activity was carried out by a team of lecturers and students of Majapahit Health Sciences College as a form of community service activity. Education is carried out using technology-based learning methods through video media and leaflet for 50 minutes. The material presented includes the definition of anemia, causes of anemia, signs and symptoms of anemia, ways to prevent anemia, ways to detect anemia, and management of anemia.The partner of this community service activity is SMAN 1 Kutorejo, Mojokerto Regency. The results of this activity received a positive response from the target participants. The results obtained from this activity were: before being given health education, most of the knowledge was in the sufficient category (71%) and after being given health education, almost all of the knowledge was in the good category (82%).It is hoped that with this activity, students' knowledge can increase and can prevent anemia in adolescents.